The Critical Role of Coefficients: Updating Allometric Normalisation Constants for Modern Ecology and Modelling - Penelope S. A. Blyth; Thomas F. Johnson; Thomas Malpas; Hana Mayall; Alina Smith; Alain Danet; Eva Delmas; Christopher A. Griffiths; Benno I. Simmons; John Jackson; Ulrich Brose; Andrew P. Beckerman (Ecology Letters, 2026)
Allometry, the scaling of traits or biological rates with body mass, is central to a wide range of ecological research including dynamic food web modelling. There has been extensive focus on exponents (3/4 scaling laws), but little on the coefficients (normalisation constants). Coefficients that have been used since 2006 are derived from limited data and dated methodologies. Here, we compiled a data set of over 1000 genera with body mass spanning 10 orders of magnitude. We updated metabolism and production coefficients, deriving new genus and metabolic group levels estimates with phylogenetic hierarchical modelling providing robust inference. Our coefficients were mostly lower than those previously estimated, with increased uncertainty estimates. We used the Bioenergetic Food Web Model to evaluate their impact, finding increased biomass and species persistence but no change in stability. Our coefficients pave the way for future simulations that take advantage of subsets of genus and metabolic group data.

Coordination of care is facilitated by delayed feeding and collective arrivals in the long-tailed tit - Chay Halliwell; Andrew P. Beckerman; Sarah J. Biddiscombe; Marion Germain; Ben J. Hatchwell (Animal Behaviour, 2023)

The context dependency of multiple stressor effects on biodiversity: A commentary on Kefford et al. (2022) - Andrew P. Beckerman (Global Change Biology, 2023)

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Bridging gaps in demographic analysis with phylogenetic imputation - Tamora D. James; Roberto Salguero‐Gómez; Owen R. Jones; Dylan Z. Childs; Andrew P. Beckerman (Conservation Biology, 2021)
Phylogenetically informed imputation methods have rarely been applied to estimate missing values in demographic data but may be a powerful tool for reconstructing vital rates of survival, maturation, and fecundity for species of conservation concern. Imputed vital rates could be used to parameterize demographic models to explore how populations respond when vital rates are perturbed. We used standardized vital rate estimates for 50 bird species to assess the use of phylogenetic imputation to fill gaps in demographic data. We calculated imputation accuracy for vital rates of focal species excluded from the data set either singly or in combination and with and without phylogeny, body mass, and life‐history trait data. We used imputed vital rates to calculate demographic metrics, including generation time, to validate the use of imputation in demographic analyses. Covariance among vital rates and other trait data provided a strong basis to guide imputation of missing vital rates in birds, even in the absence of phylogenetic information. Mean NRMSE for null and phylogenetic models differed by λ > 0.8). In these cases, including body mass and life‐history trait data compensated for lack of phylogenetic information: mean normalized root mean square error (NRMSE) for null and phylogenetic models differed by

Evaluating additive versus interactive effects of copper and cadmium on Daphnia pulex life history - Shlair A. Sadeq; Andrew P. Beckerman (Environmental Science and Pollution Research, 2020)
A key challenge of standard ecotoxicological risk assessment is to predict the sub-lethal risk of multiple contaminants on aquatic organisms. Our study assessed the sub-lethal mixture toxicity of copper (Cu) and cadmium (Cd) on Daphnia pulex and included manipulations of food level and assessment of three genotypes. We investigated the interaction between essential (Cu) and non-essential (Cd) metals on ingestion rate, reproduction, maturation time, size at maturity and somatic growth rate of three D. pulex genotypes, over 21 days and under standard and high food conditions. We explored the potential interaction of the metals on ingestion and life history by implementing a response surface experimental design combining control and two levels of Cu and Cd and their combinations. Overall, both metals reduced ingestion rates, reduced reproduction, delayed maturation, reduced body size at maturity and lowered somatic growth rate. Our results further indicated pervasive interactions between the metals; numerous instances where the effects of each metal were non-linear; the effect of a metal varied by D. pulex food levels (ingestion rate and size at maturity), and the effect of a metal varied by genotypes (reproduction). Apart from the maturation time and somatic growth rate, our results suggest that life history traits are affected in non-additive ways by three factors that are often discussed and rarely estimated together: mixtures of metals, genotypes and resource levels. Our data that are derived from exposing daphnids to two metals highlight how metals interact with each other and the context of food resource and genetic variation. While interactions make it harder to generate predictions, and ultimately water quality regulations about the effects of metals, those detected in this study appear to be tractable.

The Chronic Effects of Copper and Cadmium on Life History Traits Across Cladocera Species: A Meta-analysis - Shlair A. Sadeq; Andrew P. Beckerman (Archives of Environmental Contamination and Toxicology, 2019)

The impact of intraspecific variation on food web structure - Tom Clegg; Mohammad Ali; Andrew P. Beckerman (Ecology, 2018)
Accounting for the variation that occurs within species in food webs can theoretically result in significant changes in both network structure and dynamics. However, there has been little work exploring their role with empirical data. In particular, the variation associated with species’ life cycles, which is prevalent and represents both trait variation and taxonomic identity, has received little attention. Here, we characterize the structural consequences of life stage variation in five food webs, including a newly compiled web from the Arabian Gulf. We show that making life stage variation explicit in food webs results in larger food webs that possess consistent structural changes that are separate from the changes in structure that come simply from increasing the number of nodes in the webs. Furthermore, we show that the magnitude of these changes is related to ontogenetic specialism, the degree of overlap in the ecological niches of life stages. These results demonstrate the capacity of intraspecific variation to affect ecological networks and indicate the potential usefulness of stage‐structured food webs, which capture size and taxonomic information, to represent variation below the species level.

The Andes Cordillera. Part IV: spatio‐temporal freshwater run‐off distribution to adjacent seas (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Andrew P. Beckerman; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
The spatio‐temporal freshwater river run‐off pattern from individual basins, including their run‐off magnitude and change (1979/1980–2013/2014), was simulated for the Andes Cordillera west of the Continental Divide in an effort to understand run‐off variations and freshwater fluxes to adjacent fjords, Pacific Ocean, and Drake Passage. The modelling tool SnowModel/HydroFlow was applied to simulate river run‐off at 3‐h intervals to resolve the diurnal cycle and at 4‐km horizontal grid increments using atmospheric forcing from NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) data sets. Simulated river run‐off hydrographs were verified against independent observed hydrographs. For the domain, 86% of the simulated run‐off originated from rain, 12% from snowmelt, and 2% from ice melt, whereas for Chile, the water‐source distribution was 69, 24, and 7%, respectively. Along the Andes Cordillera, the 35‐year mean basin outlet‐specific run‐off (L s −1 km −2 ) showed a characteristic regional hourglass shape pattern with highest run‐off in both Colombia and Ecuador and in Patagonia, and lowest run‐off in the Atacama Desert area. An Empirical Orthogonal Function analysis identified correlations between the spatio‐temporal pattern of run‐off and flux to the El Niño Southern Oscillation Index and to the Pacific Decadal Oscillation.

Erratum to: The use of natural infochemicals for sustainable and efficient harvesting of the microalgae Scenedesmus spp. for biotechnology: insights from a meta-analysis - Sebastiana Roccuzzo; Andrew P. Beckerman; Jagroop Pandhal (Biotechnology Letters, 2017)

The use of natural infochemicals for sustainable and efficient harvesting of the microalgae Scenedesmus spp. for biotechnology: insights from a meta-analysis - Sebastiana Roccuzzo; Andrew P. Beckerman; Jagroop Pandhal (Biotechnology Letters, 2016)

The ecological forecast horizon, and examples of its uses and determinants - Owen L. Petchey; Mikael Pontarp; Thomas M. Massie; Sonia Kéfi; Arpat Ozgul; Maja Weilenmann; Gian Marco Palamara; Florian Altermatt; Blake Matthews; Jonathan M. Levine; Dylan Z. Childs; Brian J. McGill; et al. (Ecology Letters, 2015)
Forecasts of ecological dynamics in changing environments are increasingly important, and are available for a plethora of variables, such as species abundance and distribution, community structure and ecosystem processes. There is, however, a general absence of knowledge about how far into the future, or other dimensions (space, temperature, phylogenetic distance), useful ecological forecasts can be made, and about how features of ecological systems relate to these distances. The ecological forecast horizon is the dimensional distance for which useful forecasts can be made. Five case studies illustrate the influence of various sources of uncertainty (e.g. parameter uncertainty, environmental variation, demographic stochasticity and evolution), level of ecological organisation (e.g. population or community), and organismal properties (e.g. body size or number of trophic links) on temporal, spatial and phylogenetic forecast horizons. Insights from these case studies demonstrate that the ecological forecast horizon is a flexible and powerful tool for researching and communicating ecological predictability. It also has potential for motivating and guiding agenda setting for ecological forecasting research and development.

Greenland precipitation trends in a long‐term instrumental climate context (1890–2012): evaluation of coastal and ice core records - Sebastian H. Mernild; Edward Hanna; Joseph R. McConnell; Michael Sigl; Andrew P. Beckerman; Jacob C. Yde; John Cappelen; Jeppe K. Malmros; Konrad Steffen (International Journal of Climatology, 2015)
Here, we present an analysis of monthly, seasonal, and annual long‐term precipitation time‐series compiled from coastal meteorological stations in Greenland and Greenland Ice Sheet ( GrIS ) ice cores (including three new ice core records from ACT11D , Tunu2013, and Summit2010). The dataset covers the period from 1890 to 2012, a period of climate warming. For approximately the first decade of the new millennium (2001–2012) minimum and maximum mean annual precipitation conditions are found in Northeast Greenland (Tunu2013 c. 120 mm water equivalent (w.e.) year −1 ) and South Greenland (Ikerasassuaq: c. 2300 mm w.e. year −1 ), respectively. The coastal meteorological stations showed on average increasing trends for 1890–2012 (3.5 mm w.e. year −2 ) and 1961–2012 (1.3 mm w.e. year −2 ). Years with high coastal annual precipitation also had a: (1) significant high number of precipitation days ( r 2 = 0.59); and (2) high precipitation intensity measured as 24‐h precipitation ( r 2 = 0.54). For the GrIS the precipitation estimated from ice cores increased on average by 0.1 mm w.e. year −2 (1890–2000), showing an antiphase variability in precipitation trends between the GrIS and the coastal regions. Around 1960 a major shift occurred in the precipitation pattern towards wetter precipitation conditions for coastal Greenland, while drier conditions became more prevalent on the GrIS . Differences in precipitation trends indicate a heterogeneous spatial distribution of precipitation in Greenland. An Empirical Orthogonal Function analysis reveals a spatiotemporal cycle of precipitation that is linked instantaneously to the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation and with an ∼6 years lag time response to the Greenland Blocking Index.

Endocrine regulation of predator-induced phenotypic plasticity - Stuart R. Dennis; Gerald A. LeBlanc; Andrew P. Beckerman (Oecologia, 2014)

Latitude or biogeographic breaks? Determinants of phenotypic (co)variation in fitness-related traits in Betaeus truncatus along the Chilean coast - Aura M. Barria; Marco A. Lardies; Andrew P. Beckerman; Leonardo D. Bacigalupe (Marine Biology, 2014)

Quantifying multivariate plasticity: genetic variation in resource acquisition drives plasticity in resource allocation to components of life history - Matthew R. Robinson; Andrew P. Beckerman (Ecology Letters, 2013)
Acquisition and allocation of resources are central to life‐history theory. However, empirical work typically focuses only on allocation despite the fact that relationships between fitness components may be governed by differences in the ability of individuals to acquire resources across environments. Here, we outline a statistical framework to partition the genetic basis of multivariate plasticity into independent axes of genetic variation, and quantify for the first time, the extent to which specific traits drive multitrait genotype–environment interactions. Our framework generalises to analyses of plasticity, growth and ageing. We apply this approach to a unique, large‐scale, multivariate study of acquisition, allocation and plasticity in the life history of the cricket, Gryllus firmus . We demonstrate that resource acquisition and allocation are genetically correlated, and that plasticity in trade‐offs between allocation to components of fitness is 90% dependent on genetic variance for total resource acquisition. These results suggest that genotype–environment effects for resource acquisition can maintain variation in life‐history components that are typically observed in the wild.

Reciprocity in predator–prey interactions: exposure to defended prey and predation risk affects intermediate predator life history and morphology - Edd Hammill; Andrew P. Beckerman (Oecologia, 2010)

Climate warming strengthens indirect interactions in an old‐field food web - Brandon T. Barton; Andrew P. Beckerman; Oswald J. Schmitz (Ecology, 2009)
Climate change is expected to alter trophic interactions within food chains, but predicting the fate of particular species is difficult because the predictions hinge on knowing exactly how climate influences direct and indirect interactions. We used two complementary approaches to examine how climate change may alter trophic interactions within an old‐field food web composed of herbaceous plants, grasshopper herbivores, and spider predators. We synthesized data spanning 15 years of experimentation during which interannual mean growing season temperature varied by 2°C and precipitation by 2.5 cm. We also manipulated temperature within mesocosms to test the affect of temperature on primary production and strength of direct and indirect trophic interactions. Both approaches produced similar results: plant production was not directly affected by temperature or precipitation, but the strength of top‐down indirect effects on grasses and forbs increased by 30–40% per 1°C. Hence, the net effect of climate change was to strengthen top‐down control of this terrestrial system.

Combined use of pheromone trails and visual landmarks by the common garden ant Lasius niger - Sophie E. F. Evison; Owen L. Petchey; Andrew P. Beckerman; Francis L. W. Ratnieks (Behavioral Ecology and Sociobiology, 2008)

Behavioural versus physiological mediation of life history under predation risk - Andrew P. Beckerman; Kazimierz Wieski; Donald J. Baird (Oecologia, 2007)

Oil pollution and climate have wide‐scale impacts on seabird demographics - Stephen C. Votier; Ben J. Hatchwell; Andrew Beckerman; Robin H. McCleery; Fiona M. Hunter; Jayne Pellatt; Mark Trinder; Tim R. Birkhead (Ecology Letters, 2005)
Oil spills often spell disaster for marine birds caught in slicks. However, the impact of oil pollution on seabird population parameters is poorly known because oil spills usually occur in wintering areas remote from breeding colonies where birds may be distributed over a wide area, and because it is difficult to separate the effects of oil pollution from the effect of natural environmental variation on seabird populations. Using a long‐term data set we show that over‐winter survival of adult common guillemots ( Uria aalge ) is negatively affected by both the incidence of four major oil‐spills in their wintering grounds and high values of the North Atlantic Oscillation (NAO) index. After controlling for the effect of the NAO index, we show that winter mortality of adult guillemots is doubled by major oil pollution incidents. Our results demonstrate that oil pollution can have wide‐scale impacts on marine ecosystems that can be quantified using populations of marked individuals to estimate survival.

The combined effects of energy and disturbance on species richness in protist microcosms - Lianna Scholes; Philip H. Warren; Andrew P. Beckerman (Ecology Letters, 2005)
The supply of energy, and the frequency of disturbance can both affect species diversity, often, although not always, producing unimodal diversity patterns along an energy or disturbance gradient. However, it has been suggested that diversity is a combined function of both factors, and the dynamic equilibrium model proposed by Huston (1979) is one formalization of this suggestion. This idea has received little direct testing. Here we carry out such a test using protist microcosms, in a factorial manipulation of six levels of energy (quantity of organic resource) and five levels of disturbance (frequency of temperature shock). Species richness responded to both energy supply and disturbance frequency, although not always unimodally. Patterns of response changed over time, and there was some evidence of an interaction between energy and disturbance at two of six time intervals. However, the specific form of this interaction differs from that predicted by the dynamic equilibrium model, and overall, the results provide little support for the model.

Reconciling variability and optimal behaviour using multiple criteria in optimization models - OSWALD J. Schmitz; JARED L. Cohon; KRISTINA D. Rothley; ANDREW P. Beckerman (Evolutionary Ecology, 1998)

Functional responses of adaptive consumers and community stability with emphasis on the dynamics of plant-herbivore systems - Oswald J. Schmitz; Andrew P. Beckerman; Sacha Litman (Evolutionary Ecology, 1997)